Mechanisms of plant acclimation to multiple abiotic stresses - Zhang Jiang; Martijn van Zanten; Rashmi Sasidharan (Communications Biology)
Abstract Plants frequently encounter a range of abiotic stresses and their combinations. Even though stresses rarely occur in isolation, research on plant stress resilience typically focuses on single environmental stressors. Plant responses to abiotic stress combinations are often distinct from corresponding individual stresses. Factors determining the outcomes of combined stresses are complex and multifaceted. In this review, we summarize advancements in our understanding of the mechanisms underlying plant responses to co-occurring (combined and sequential) abiotic stresses, focusing on morphological, physiological, developmental, and molecular aspects. Comprehensive understanding of plant acclimation, including the signaling and response mechanisms to combined and individual stresses, can contribute to the development of strategies for enhancing plant resilience in dynamic environments.